2009
DOI: 10.1167/iovs.09-3408
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Noncontact Pachymetry after Laser In Situ Keratomileusis

Abstract: Both noncontact pachymeters provide repeatable CCT measurements in transparent postmyopic LASIK corneas after the early postoperative period. Intersession variations in CCT of more than 29 microm with the Orbscan II and 19 microm with the Topcon SP-2000P may reflect true corneal change. These estimates should help investigators and clinicians differentiate actual CCT modification from measurement variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
0
9
1
Order By: Relevance
“…For CCT measurements, the 95% LoA using a single Scheimpflug imaging system, noncontact specular microscope (EM-3000, Tomey Corp.), and combined scanning-slit and Placido-disk topographer (Orbscan II, Bausch & Lomb) were reported to be À9.2 to 9.5 mm, À25.13 to 18.06 mm, and À32.1 to 26.4 mm, respectively. [19][20][21] In addition, Ali o and Piñero 22 found a significant corneal flap thickness variation after laser in situ keratomileusis of À9 mm to 37 mm, À12 mm to 31 mm, À9 mm to 23 mm using the M2 microkeratome (Moria), the Carriazo-Pendular microkeratome (Schwind Eye-Tech-Solutions GmbH & Co. KG), and the Intralase femtosecond laser (Abbott Medical Optics, Inc.), respectively. A meta-analysis showed the SD of the CCT in normal eyes is 31 mm.…”
Section: Discussionmentioning
confidence: 99%
“…For CCT measurements, the 95% LoA using a single Scheimpflug imaging system, noncontact specular microscope (EM-3000, Tomey Corp.), and combined scanning-slit and Placido-disk topographer (Orbscan II, Bausch & Lomb) were reported to be À9.2 to 9.5 mm, À25.13 to 18.06 mm, and À32.1 to 26.4 mm, respectively. [19][20][21] In addition, Ali o and Piñero 22 found a significant corneal flap thickness variation after laser in situ keratomileusis of À9 mm to 37 mm, À12 mm to 31 mm, À9 mm to 23 mm using the M2 microkeratome (Moria), the Carriazo-Pendular microkeratome (Schwind Eye-Tech-Solutions GmbH & Co. KG), and the Intralase femtosecond laser (Abbott Medical Optics, Inc.), respectively. A meta-analysis showed the SD of the CCT in normal eyes is 31 mm.…”
Section: Discussionmentioning
confidence: 99%
“…A biometric parameter commonly reported in the literature is the central corneal thickness (CCT) which may be used to evaluate normal corneal development and to diagnose a variety of ocular/corneal pathologies (Ashwin et al, 2009; Doughty and Zaman, 2000; Fontes et al, 2010; Hager et al, 2009; Insull et al, 2010; Montiani-Ferreira et al, 2003) as well as pre- and post-surgical conditions (Maldonado et al, 2009). It is also a consideration in contact lens fitting and continuing care for contact lens wearers (Martin et al, 2007; Oh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2 The main limitation of the current study is that the reason for the variability between measurements showed a wide distribution between methods was not completely addressed, although it can be explained by the measurement repeatability of Orbscan-II being generally lower than that of Topcon NCSM in postmyopic LASIK patients. 35 In addition, this study included only patients who had undergone LASIK to treat myopia, and, therefore, the conclusions cannot be applied to patients with hyperopia, in whom the postoperative corneal shape is more prolate. Finally, ultrasonic pachymetry was not performed in the study eyes, thus precluding direct comparison of both non-contact methods with the gold standard in order to find out which of the two is closer to the 'true' value.…”
Section: Discussionmentioning
confidence: 99%